2008
DOI: 10.1103/physrevb.77.045308
|View full text |Cite
|
Sign up to set email alerts
|

Ge vacancies atGeSiinterfaces: Stress-enhanced pairing distortion

Abstract: We have performed first-principles total-energy electronic-structure calculations based on the densityfunctional theory to clarify energetics and electron states of the Ge vacancies in strained Ge layers on the Si͑001͒ surface. We find that pairing distortion is a principal relaxation pattern around the vacancies. The pairing of the two atoms located on either ͑110͒ or ͑110͒ plane is remarkably enhanced due to compressed strain in the lateral plane. It is found that the enhanced pairing causes reduction of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…First, we show the results of biaxial strain. We investigated the strained Ge films on Si substrates (5). We have found that the formation energies of vacancies in the strained Ge are about 1.5 eV, and these formation energies are substantially smaller compared with that in bulk Ge (2.7 eV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we show the results of biaxial strain. We investigated the strained Ge films on Si substrates (5). We have found that the formation energies of vacancies in the strained Ge are about 1.5 eV, and these formation energies are substantially smaller compared with that in bulk Ge (2.7 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Now the enhancement of mobility is observed in strained materials, so heterostructures consisting of Si and Ge have been attracting much greater attention regarding one of promising boosters for post-scaling Si technology (4). However, there are a few reports related to atomic and electronic structures of Ge defects under strain in spite of their importance, although we have theoretically reported the Ge vacancies under biaxial strain (5). In this paper, we investigate the energetics and atomic and electronic structures of Ge mono-vacancies under compressive strain.…”
Section: Introductionmentioning
confidence: 97%